Zhongguo wen hua sheng cheng shi. - Feng, Tianyu, 1942-2023, author. Link Link
1 online resource (508 pages)
Keywords: This book affords a macro-level study of the evolution of Chinese culture by examining the harmonious interplay between humans and nature, humans and society, and humans and the self, while exploring its profound implications for modern civilisation and cross-cultural dialogue.